Tính \(L=\lim\left(\sqrt{n^2+2n-1}-\sqrt{2n^2+n}\right)\).
\(-1\) | |
\(1-\sqrt{2}\) | |
\(-\infty\) | |
\(+\infty\) |
Chọn phương án C.
Dùng máy tính cầm tay:
Chọn phương án C.
\(\begin{aligned}
L&=\lim\left(\sqrt{n^2+2n-1}-\sqrt{2n^2+n}\right)\\
&=\lim\left(\sqrt{n^2\left(1+\dfrac{2}{n}-\dfrac{1}{n^2}\right)}-\sqrt{n^2\left(2+\dfrac{1}{n}\right)}\right)\\
&=\lim\left(n\sqrt{1+\dfrac{2}{n}-\dfrac{1}{n^2}}-n\sqrt{2+\dfrac{1}{n}}\right)\\
&=\lim n\cdot\left(\sqrt{1+\dfrac{2}{n}-\dfrac{1}{n^2}}-\sqrt{2+\dfrac{1}{n}}\right)\\
&=-\infty.
\end{aligned}\)
Vì \(\begin{cases}
\lim n&=+\infty\\
\lim\left(\sqrt{1+\dfrac{2}{n}-\dfrac{1}{n^2}}-\sqrt{2+\dfrac{1}{n}}\right)&=1-\sqrt{2}<0.
\end{cases}\)